The effects of midazolam-ketamine and xvlazine-ketamine on arterial blobd pressure and blood gases in dogs - Yılmaz Koç; Mustafa Kul; Fahrettin Alkan; Zeki Oğurtan (Eurasian Journal of Veterinary Sciences)
The effects of midazolam-kelamine (M-K) and xylazine-ketamine (X-K) combinations on arterial blood pressures and blood gases of 12 dogs were evaluated in this study, Alt baseline measurements were made before the anesthesia as baseline values, and all measurements were repeated at 15, 30, 60, 90, and 120 minutes intervals after Ihe anesthesia. While the heart and breathing rates increased in the M-K group of dogs, there was a decrease in the X-K group of dogs with the statistical significant difference (p<0.05). The difference between the sıstoüc and diastolic arterial blood pressures was not statistically significant between the two group of dogs. On the other hand. The mean blood pressures at the 90 and 120 minutes were statistically significant (p<0,05). While there was no sta tistically significant difference on the arterial PaC02 and Pa02, there was a statistically significant difference on pH at the 15 (p<0.01) and 30 (p<0.05) minutes between the two groups of dogs.